Investigating the relationship between burnout, internalized shame and metacognitive beliefs on emotion regulation in women affected by marital infidelity - Jafari, Tayyebeh; Zarei, Maryam; Nazari Shahraki, Mandana; Amani, Omid (Psychology of Woman Journal, 2023)
Objective: This research investigated the relationship between boredom, internalized shame, and metacognitive beliefs on emotion regulation in women affected by marital infidelity. Method: The research method was descriptive and correlational. The statistical population included all betrayed women in Tehran province in 2022; 242 were selected by snowball sampling method. Cook’s (1988) Internalized Shame Scale (ISS), Garnefski, Kraaij & Spinhoven’s (2001) Cognitive Emotion Regulation Questionnaire (CERQ), Cartwright-Hatton, Wells’ Meta-Cognitions Questionnaire (MCQ) and Pines’ (1996) Couple Burnout Measure (CBM) were used to collect information. The data were analyzed with with SMART-PLS and SPSS-22 software using SEM method. Results: The findings showed a significant relationship between internalized shame, metacognitive belief, and fear with emotion regulation. The results show that betrayed women express their positive emotions less and express positive emotions less often. Conclusion: Various factors are involved in controlling these women’s feelings and emotions, which requires more consideration in examining these factors to help this vulnerable group.